At være er at være set - et visuelt perspektiv på sociale positioner - Camilla Elg (The Royal Danish Library, 2009)
To be is to be seen - a visuel perspective at social positionsThis article claims that a strengthening of the emphasis on visual embodiment in the analysis of social positions is much needed. It works with the application of an analytic framework inspired by theories of ‘the mimetic faculty' and phenomenological theories of embodiment. This creates a focus on experiences of being seen; experiences of one's ‘seenness'. With an empirical illustrative case, the article shows how this framework makes it possible to address feelings and sensations that are formative of the experience of one's own individual position.